5+3g=-1=2g

Simple and best practice solution for 5+3g=-1=2g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3g=-1=2g equation:



5+3g=-1=2g
We move all terms to the left:
5+3g-(-1)=0
We add all the numbers together, and all the variables
3g+6=0
We move all terms containing g to the left, all other terms to the right
3g=-6
g=-6/3
g=-2

See similar equations:

| -1/5y=-29 | | 210=10.w.3 | | n-10/2=-15 | | n-10÷2=-15 | | k-10=2+7k | | 14+3n=5; | | 11x+44=-11 | | p+5=2p | | -6t-6=-5t | | 6x-4(-14)=30 | | -6t−6=-5t | | -x^2-2x+1x=-4 | | 7-6b=-5b | | -10-10v=-5v | | -10−10v=-5v | | -1-2r=-3r | | 32r+500=55r | | 3(6x-5)+5(x-2)=-48 | | 6h=8h+6 | | 5×+4=7x-10 | | 15p6=21 | | 3x+10=3x-28=180 | | 48=6(n+7)-3(-1+3n) | | 16p6=21 | | -2x+4x-7+2=2x+4-9 | | 3(4x-5)=2(3x+9) | | -45=-5(x-7)+7(6-8x) | | -45=-5(x+7)+7(6-8x) | | 8x+4+2=4x+4x-7 | | -4(1+3x)+2(7-8x)=38 | | 5k-20=3k | | -8(-8+8m)-3(m-7)=18 |

Equations solver categories